LONG HUFF & PUFF APLICATION FOR A BETTER STEAM SWEEP AT AN INVERTED 7 SPOT PATTERN CASE STUDY AREA X Y FIELD - ARYANTI (NIM : 22207323), LYSA
Pattern flood injection technique is applied in Y field development. Area X, as a focus area of study has 7 spot inverted pattern where one injection well is dedicated to six producer wells in a hexagonal pattern shape. Along with the injection period, it is often found that steam growth is not in balance toward the whole area within the pattern. Once the steam reached one or more producer well in the pattern, steam tends to follow through that same direction and need long time for other producer wells to be swept by the steam. One of the strategy that is implemented for a better steam sweep is Long Huff & Puff that is used to accelerate steam breakthrough at target wells. The main purpose of Long Huff & Puff implementation is to connect steam front from an injection well to a producer well by continuosly injecting steam at the producer well while the injection is maintaned at the injector well (two direction steam injection). By injecting steam from two directions, there will be a continous steam zone between producer and injector wells. The methodology used to calculate steam and heat requirement is based on Neuman equation. By measuring distance from steam front to producer well, steam required and injection time could be calculated. Marx - Langenheim equation also used to calculate injection time, as a comparison with the Neuman method. Case study conducted on three producer wells in Area X shows a significant wellhead temperature increase, from 144 - 173 oF before injection up to 222 - 260 oF after injection. Increase in temperature will impact oil production increase. Total oil production from this three wells before Long Huff & Puff is 142 BOPD and after Long Huff & Puff is 356 BOPD. Economic calculation of this study shows that all of the candidates are economic to have Long Huff & Puff, where the economic indocators show the NPV is around US$ 199 M - US$ 630 M and DPI is around 1.98 - 4.1.